The wondrous workings of planet Earth : understanding our world and its ecosystems - Ignotofsky, Rachel, 1989- (Ten Speed Press, 2018)
Presents infographics detailing the science of ecology, showing how every living organism on Earth is connected through the biosphere down through biomes, ecosystems, living communities, species groups, and individuals. Discusses how what happens to one part of the planet affects all the others, the cycles of nature, climate change, pollution, and what human beings can do to help keep the planet healthy and living. Includes a glossary.